Relatório de estágio supervisionado obrigatório: diretoria executiva de meio ambiente e urbanismo prefeitura municipal de Mossoró – RN - Bastos, Achilles Pinheiro (Universidade Federal Rural do Semi-Árido, 2020)
Environmental education transforms values and attitudes through the construction of new habits and knowledge, raising awareness of the integrated relationships of human beings, society and nature, aiming at local and global balance, improving quality in all stages of life. The objective of the internship was to develop pedagogical practices of Environmental Education at the Monsenhor Mota Municipal School in the municipality of Mossoró - RN, using as a strategy the creation, development and cultivation of vegetables and fruit tree species. The work was coordinated by the Executive Management of Environmental Education (GEEA) that is part of the Executive Directorate for Environment and Urbanism, which in turn is part of the Municipal Secretariat for Infrastructure, Environment, Urbanism and Urban Services - SEIMURB. The accomplishment of this work in the area of environmental education enabled the aggregation and exchange of practical knowledge in the area of nature conservation, enabling the insertion of forest engineering in the school environment, thus assisting the professionals of the education network in carrying out their daily activities, providing to students the incentive to investigate, the stimulus to questioning, the use of resources besides the textbook and the performance of activities outside the classroom.
Keywords: Arborização; Educação básica; Práticas pedagógicas; Afforestation; Basic education; Pedagogical practices; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL